Corals concentrate dissolved inorganic carbon to facilitate calcification - Allison, Nicola; Cohen, I.; Finch, Adrian Anthony; Erez, J.; Tudhope, A.W.; Edinburgh Ion Microprobe Facility (Nature Communications, 2015)
This work was supported by the UK Natural Environment Research Council (awards NER/A/S/2003/00473 and NE/G015791/1 to N.A. and A.A.F.; NER/GR3/12021 to A.W.T.). Participation of J.E. and I.C. in this study was supported by DFG project Trion and the Israel Science Foundation (grants 870/05 and 551/10). The sources of dissolved inorganic carbon (DIC) used to produce scleractinian coral skeletons are not understood. Yet this knowledge is essential for understanding coral biomineralization and assessing the potential impacts of ocean acidification on coral reefs. Here we use skeletal boron geochemistry to reconstruct the DIC chemistry of the fluid used for coral calcification. We show that corals concentrate DIC at the calcification site substantially above seawater values and that bicarbonate contributes a significant amount of the DIC pool used to build the skeleton. Corals actively increase the pH of the calcification fluid, decreasing the proportion of DIC present as CO2 and creating a diffusion gradient favouring the transport of molecular CO2 from the overlying coral tissue into the calcification site. Coupling the increases in calcification fluid pH and [DIC] yields high calcification fluid [CO32-] and induces high aragonite saturation states, favourable to the precipitation of the skeleton. Peer reviewed